Nepenthes × ventrata Transcriptome Profiling Reveals a Similarity Between the Evolutionary Origins of Carnivorous Traps and Floral Organs - Shchennikova, Anna V.; Beletsky, Alexey V.; Filyushin, Mikhail A.; Slugina, Maria A.; Gruzdev, Eugeny V.; Mardanov, Andrey V.; Kochieva, Elena Z.; Ravin, Nikolay V. (Frontiers in Plant Science, 2021)
The emergence of the carnivory syndrome and traps in plants is one of the most intriguing questions in evolutionary biology. In the present study, we addressed it by comparative transcriptomics analysis of leaves and leaf-derived pitcher traps from a predatory plant Nepenthes ventricosa × Nepenthes alata. Pitchers were collected at three stages of development and a total of 12 transcriptomes were sequenced and assembled de novo. In comparison with leaves, pitchers at all developmental stages were found to be highly enriched with upregulated genes involved in stress response, specification of shoot apical meristem, biosynthesis of sucrose, wax/cutin, anthocyanins, and alkaloids, genes encoding digestive enzymes (proteases and oligosaccharide hydrolases), and flowering-related MADS-box genes. At the same time, photosynthesis-related genes in pitchers were transcriptionally downregulated. As the MADS-box genes are thought to be associated with the origin of flower organs from leaves, we suggest that Nepenthes species could have employed a similar pathway involving highly conserved MADS-domain transcription factors to develop a novel structure, pitcher-like trap, for capture and digestion of animal prey during the evolutionary transition to carnivory. The data obtained should clarify the molecular mechanisms of trap initiation and development and may contribute to solving the problem of its emergence in plants.